Pemanfaatan E-Learning dalam Meningkatkan Perilaku Kewarganegaraan Anak Sekolah Dasar - Jusman Jusman (Journal of Humanities, Social Sciences, and Education, 2025)
The development of digital technology has brought significant changes to the world of education, including civics learning in elementary schools. One innovation currently experiencing rapid growth is the use of e-learning. This literature review aims to critically examine the role of e-learning in improving the civic behavior of elementary school children. Various studies have shown that e-learning serves not only as a medium for conveying information but also fosters active participation, collaboration, and awareness of the values ​​of democracy, tolerance, and social responsibility. Through the interactive approach offered by e-learning platforms, students can learn to understand civic concepts contextually, whether through simulations, online discussions, or digital project-based activities. Thus, e-learning has the potential to develop more meaningful civic behavior, especially in a technology-savvy generation. However, its implementation still requires the support of teachers, parents, and school policies so that the use of e-learning is not solely oriented towards cognitive aspects but also internalizes civic values ​​in students' daily lives. The results of this study confirm that e-learning is a strategic medium for developing civic behavior relevant to the needs of 21st-century education, although challenges such as limited internet access, digital literacy, and teacher preparedness still require further attention.